2021
DOI: 10.1371/journal.pone.0254450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mass spectrometry MS/MS spectra for the presence of isopeptide crosslinked peptides

Abstract: Isopeptide crosslinked proteins can be the product of transglutaminase or of exposure to organophosphorus toxicants (OP). Transglutaminase links glutamine to lysine with loss of ammonia. OP toxicants induce a link between glutamic acid and lysine with loss of water. Our goal was to establish criteria to distinguish real from false isopeptide crosslinks reported by software searches of mass spectrometry data. We used fragmentation spectra of tryptic peptides from MAP-rich tubulin Sus scrofa as a test system for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…A diethylphospho-adduct was found on lysine 163, supporting its involvement in cross-linking. The MSMS spectrum for this latter cross-linked peptide pair was previously published . A cross-link between K336 in peptide DVNAAIATIK 336 TK from tubulin α1A and E158 in peptide EE 158 YPDR from tubulin β4B appeared two times (in charge state 3, from gel slices A and B).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…A diethylphospho-adduct was found on lysine 163, supporting its involvement in cross-linking. The MSMS spectrum for this latter cross-linked peptide pair was previously published . A cross-link between K336 in peptide DVNAAIATIK 336 TK from tubulin α1A and E158 in peptide EE 158 YPDR from tubulin β4B appeared two times (in charge state 3, from gel slices A and B).…”
Section: Resultsmentioning
confidence: 82%
“…The MSMS spectrum for this latter cross-linked peptide pair was previously published. 22 A cross-link between K336 in peptide DVNAAIATIK 336 TK from tubulin α1A and E158 in peptide EE 158 YPDR from tubulin β4B appeared two times (in charge state 3, from gel slices A and B). K336 in peptide DVNAAIATIK 336 TK from tubulin α1A was also cross-linked to D98 in peptide ED 98 AANNYAR from tubulin α1A two times (in charge state 3 from gel slices A and B).…”
Section: Resultsmentioning
confidence: 99%
“…In Figure B (lane 7), CPO-treated tubulin has been transformed from its original 50 kDa mass to high-molecular-weight aggregates. In previous reports, , we showed that CPO catalyzes the formation of covalent isopeptide cross-links between diethoxyphospholysine and glutamic acid or diethoxyphospholysine and aspartic acid, with the release of diethoxyphosphate. The cross-linking reaction results in high-molecular-weight protein aggregates.…”
Section: Resultsmentioning
confidence: 90%
“…Not all diethoxyphospholysine adducts participate in a cross-linking reaction; those that retain the adduct are detectable by mass spectrometry. 13 To date, we have not observed a cross-linking reaction involving diethoxyphosphotyrosine adducts.…”
Section: Resultsmentioning
confidence: 93%
“…Although this result demonstrates the ability of the method to correctly identify transglutaminase cross-linked peptides, the optimal MS conditions and software identification parameters have not been discussed. A study conducted by Schopfer et al [ 48 ] demonstrates how a naturally occurring TG cross-link can be successfully identified by comparing its fragmentation spectrum with that of an identical synthetic peptide by using Protein Prospector [ 49 ]. However, this study focuses rather on selecting reliable identifications based on predetermined quality criteria for the MS/MS spectra than finding optimal fragmentation conditions.…”
Section: Discussionmentioning
confidence: 99%